2005
DOI: 10.1175/mwr3001.1
|View full text |Cite
|
Sign up to set email alerts
|

A Refractive Index Mapping Operator for Assimilation of Occultation Data

Abstract: This paper describes the details of a fast, linear, forward-inverse refractive index mapping operator that can be used for assimilation of occultation data of various kinds into NWP models. Basically, the mapping consists of the integration of the refractive index along finite straight lines, mimicking the observational geometry as well as the subsequent retrieval of a refractive index profile, assuming spherical symmetry. Line integrals are discretized such that the refractivity is evaluated along the horizon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 56 publications
0
35
0
Order By: Relevance
“…Foelsche et al: Errors in GNSS radio occultation data study. Later works by Sokolovskiy et al (2005) and Syndergaard et al (2005) developed so-called non-local observation operators and showed that these representativeness errors can be significantly reduced in future data assimilation systems by interpreting the retrieved profiles as complicated weighted averages of the three-dimensional atmospheric field. Since the contribution is focused around the tangent point of each ray (the point of closest approach), RO measurements can alternatively be regarded as profiles that follow the tangent point trajectory (TPT), but only in case of spherical symmetry this profile would exactly equal a profile of point measurements along the TPT.…”
Section: Introductionmentioning
confidence: 99%
“…Foelsche et al: Errors in GNSS radio occultation data study. Later works by Sokolovskiy et al (2005) and Syndergaard et al (2005) developed so-called non-local observation operators and showed that these representativeness errors can be significantly reduced in future data assimilation systems by interpreting the retrieved profiles as complicated weighted averages of the three-dimensional atmospheric field. Since the contribution is focused around the tangent point of each ray (the point of closest approach), RO measurements can alternatively be regarded as profiles that follow the tangent point trajectory (TPT), but only in case of spherical symmetry this profile would exactly equal a profile of point measurements along the TPT.…”
Section: Introductionmentioning
confidence: 99%
“…It is not obvious whether the ray tangent height error should be called an observation or forward model error, but we use the combined observation and forward model errors to weight the observations in the assimilation so the distinction is academic. Syndergaard et al (2005) recently presented a 'nonlocal' (i.e. 2D) refractivity operator.…”
Section: A Review Of 2d Gpsro Operator Researchmentioning
confidence: 99%
“…The limitation of computational resources and the timing desired for issuing forecasts encourage a more economical approach, especially after more radio occultation data become available from the COSMIC project. As a more efficient alternative to the assimilation of bending angles, Syndergaard et al (2005) and Sokolovskiy et al (2005) recently developed a new methodology, using a linearized observational operator (non-local refractivity operator) to assimilate the observed refractivity. The fractional errors of these new observables are one order of magnitude smaller than those of local refractivity.…”
Section: Introductionmentioning
confidence: 99%
“…Different methodologies have been applied to estimate observational errors (Xu et al 2001;Xu and Li 2001;Healy 2001;Zou 2002;Seemann et al 2003;Kuo et al 2004;Poli and Joiner 2004;Sokolovskiy et al 2005;Syndergaard et al 2005). Innovation vectors (i.e., observation-background) can be used to estimate the observation errors if: (i) the forecast errors are known; (ii) observation errors are independent of forecast errors; and (iii) the observations are spatially isotropic and uncor-related.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation